ERROR ANALYSIS ON THE WRITING TASKS PRODUCED BY STUDENTS OF “AZET LANGUAGE CENTRE MALANG” - SAâ€™DIAH, NIKMATUS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : error analysis, surface strategy taxonomy, source of error, writingtasksLearning a second language is difficult for learners, especially Indonesians because they must learn about grammar of the second language. The learners sometimes make an error in their learning process because they borrow the rules of their first language to the second language. Writing is the most difficult skill. Therefore, they often make some errors. The writer would like to answer three problems of this study which are: what are the types and sources of errors found on the writing tasks produced by students of “AZET Language Centre Malang” and what is the most frequent type and source of error made in the writing tasks produced by students of “AZET Language Centre Malang”. The purposes of this study are to identify the types and sources of errors found and to analyze and find the most frequent type and source of error found. This study uses surface strategy taxonomy based on Dulay’s et al theory (1982) and source of errors based on Brown (1980) and James’ theory (1998).This study uses qualitative research. The data of this study are taken from the writing tasks produced by students of “AZET Language Centre Malang”. AZET is one of the famous English courses in Malang which sends its students to study abroad. In this study, there are 10 students as the participant based on their level, period, and target to achieve the high score in IELTS. IELTS is one of the requirements to study abroad.The finding shows that based on the surface strategy taxonomy by Dulay et al (1982), there are Omission (43,1%), Misformation (39,4%), Addition (16,5%), and Misformation (1,1%). Omission has the highest number where errors occured. For the source of error based on Brown (1980) and James (1998), there are Interlingual Transfer (23,94%) and Intralingual Negative Transfer (76,1%). From this finding,  all of the students make errors and they do not apply all of the rules necessary in using the target language. It proves that it is difficult for them to achieve their high score target in IELTS.The researcher suggests the next researchers to analyze by using another theory or adding more detailed explanation in the source of error. The next researchers can also broaden the data in order to get more variety of data which are going to be analyzed.